Silicon strip defects and their impact on electrical performance of readout electronics. (24th March 2021) - Affolder, A.; Fadeyev, V.; Galloway, Z.; Gignac, M.; Gunnell, J.; Johnson, J.; Kang, N.; Kaplon, J.; Martinez-Mckinney, F.
Abstract: In preparation for the High Luminosity LHC (HL-LHC) runs, the ATLAS inner detector will be completely replaced with an all silicon Inner Tracker (ITk). Hybrid silicon pixel modules will be used for the innermost tracking layers, and silicon micro-strip detectors will be used the outer layers of the tracker. During the production of the detector, the sensors, readout electronics, and other components will undergo a series of quality control (QC) and quality assurance tests. Defects in the fabrication of the sensors will be flagged early in the manufacturer's and ATLAS QC tests. A study of the influence of sensor defects was performed to assess the characteristics of these defects in completed modules, and whether any defect posed a risk to the operation of the front-end readout electronics. All defects were found to have no impact on the performance of the front-end readout electronics for healthy amplifier channels, and defects that short the coupling between the strip implant and the metal readout electrode were only noticeable for strip leakage currents in excess of 250 nA, beyond the end-of-life currents expected for most sensors at the HL-LHC.